Efektivitas Model Pembelajaran Berasaskan Masalah Pada Sikap Siswa Terhadap Pelajaran Matematika Pada Sekolah Menengah Pertama Di Pekanbaru - Sakur ' (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
This is an experimental research using Problem Based Learning Model as atreatment. The objective of the research is identify the effectiveness of the Problem BasedLearning to student attitude toward mathematics lesson. Sample of the research 120 fromMadrasyah Tsanawiyah student in Pekanbaru. The two treatment group 60 students in eachgroup. The first treatment Group using Problem Based Learning with ‘media ceker'. Whilethe second treatment Group using treatment Problem Based Learning with 'log number line'.Instrument were used in the research of student attitude toward mathematics isquestionnaire. The research result shows that the student attitude score toward mathematicslesson post treatment more positive than before treatment.